Urgensi Pemberian Insentif Pajak Bagi Pekerja Difabel - Apelina Teresia; Shandy Jannifer Matitaputty; Agung Sugiarto (Praxis : Jurnal Sains, Teknologi, Masyarakat dan Jejaring, 2024)
Government policies and community support for providing tax incentives for workers with disabilities in Indonesia remain uncertain. This study aims to analyze public perceptions regarding the necessity of implementing tax incentives for workers with disabilities to support the disabled community in Indonesia. Data were collected through surveys and interviews, and the Analytical Hierarchy Process (AHP) was employed to determine the order of importance of various aspects related to implementing special tax measures for people with disabilities based on public perceptions. The analysis reveals that the community perceives individuals with disabilities as having lower performance and requiring support from external sources, thus warranting a comprehensive taxation scheme. The primary rationale behind the importance of this scheme is rooted in the mandate of Law Number 25 of 2009, which stipulates that employers must provide special treatment to individuals with disabilities. A crucial priority identified is the provision of special incentives for taxpayers with disabilities, as it can incentivize companies to continue offering extensive employment opportunities for this demographic